2010
DOI: 10.1029/2010gc003059
|View full text |Cite
|
Sign up to set email alerts
|

A new petrological and geophysical investigation of the present‐day plumbing system of Mount Vesuvius

Abstract: [1] A model of the electrical resistivity of Mt. Vesuvius has been elaborated to investigate the present structure of the volcanic edifice. The model is based on electrical conductivity measurements in the laboratory, on geophysical information, in particular, magnetotelluric (MT) data, and on petrological and geochemical constraints. Both 1-D and 3-D simulations explored the effect of depth, volume and resistivity of either one or two reservoirs in the structure. For each configuration tested, modeled MT tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
(224 reference statements)
2
7
0
Order By: Relevance
“…As a consequence, typical MT measurements would be hard pressed to discriminate between these models, even if they imply strong chemical variations in melt composition. This statement is in agreement with previous findings by Pommier et al [2010], who performed 3-D forward modeling considering different magma reservoirs (chamber volume up to 1000 km 3 and magma resistivity varying from 2 to 2000 ohm-m) and showed that the electrical response was only slightly affected by magma conductivity.…”
Section: Application To the Field: Imaging Magma Chambers With Magnetsupporting
confidence: 93%
See 3 more Smart Citations
“…As a consequence, typical MT measurements would be hard pressed to discriminate between these models, even if they imply strong chemical variations in melt composition. This statement is in agreement with previous findings by Pommier et al [2010], who performed 3-D forward modeling considering different magma reservoirs (chamber volume up to 1000 km 3 and magma resistivity varying from 2 to 2000 ohm-m) and showed that the electrical response was only slightly affected by magma conductivity.…”
Section: Application To the Field: Imaging Magma Chambers With Magnetsupporting
confidence: 93%
“…Hypothetical conductivity properties of a volcanic edifice [e.g., Pommier et al ., ] are presented in Table and highlight the fairly small range of conductivity variations expected. The models consider three types of melt at different temperatures, including: (1) a basaltic andesite, (2) a rhyolitic melt, and (3) a hybrid melt resulting from mixing.…”
Section: Application To the Field: Imaging Magma Chambers With Magnetmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong conductor in this figure appears to be two conductors, but this is likely an artifact caused by the 3-D nature of the dome. The conductor likely represents hot brine near the boundary of still-hot dacite intrusive rock (Palacky, 1989;Pommier et al, 2010). This finding supports a water-modulated conductiveconvective process for cooling of the intrusive body over time, a process actually measured for the 1980-86 dome by Dzurisin et al (1990).…”
Section: Where Is the Water?supporting
confidence: 67%